Energy levels structure of Pr II - Gd II ions. Issue 13 (January 2020) - Radžiūtė, L; Gaigalas, G; Rynkun, P; Kato, D; Tanaka, M
Synopsis: Observations of a kilonova associated with GW170817 provide a unique opportunity to study heavy element synthesis in the universe. However, the atomic data of r-process elements are not yet complete enough to decipher the light curves and spectral features of kilonovae. We performed extended atomic calculations for singly ionized elements with Z = 59 – 64, by employing GRASP2K package. These computations are based on strategies of Nd II published in [1]. Accuracy of data is evaluated by comparing computed energy levels with the NIST database and other authors.